Rowan of Rin - Rodda, Emily (New York : Greenwillow Books, 2001)
Because only he can read the magical map, young, weak, and timid Rowan joins six other villagers to climb a mountain and try to restore their water supply, as fears of a dragon and other horrors threaten to drive them back.
Sequel: Rowan and the Travelers.
Keywords: Heroes; Fantasy